A comparison in protein extraction from four major crop residues in Europe using chemical and enzymatic processes-a review. (January 2020) - Baker, Paul W.; Charlton, Adam
Abstract: The agricultural production of olives, rapeseed, tomatoes and citrus fruits within Europe is significant, resulting in a considerable amount of residual material. Rapeseed contains a high proportion of protein but the presence of anti-nutritional components, including glucosinolates, limits its use in food and feed applications. In contrast, the protein quantities associated with the other crop residues are much lower, although each of the residues could be separated into different constitutive parts where some have shown higher protein contents. A variety of different enzymatic based approaches to deconstruct crop residues have shown to be effective in increasing the yields of protein recovered. These studies show that valorisation of selected crop components could form the basis of a crop biorefinery process to capture proteins and other potentially useful compounds. Highlights: Separation of crop waste into different constituents containing higher protein contents High protein yields using protein protocols relying on organic solvents, alkalis and acids Proteases appear to be effective in recovering high protein yields. Lower yields with carbohydrases but functionality likely to be retained Mechanical pre-treatments can increase protein yields during an enzymatic approach.